Clinical characteristics and treatment outcomes of carbapenem-resistant Enterobacterales infections in Japan. (June 2022) - Oka, Keisuke; Matsumoto, Akane; Tetsuka, Nobuyuki; Morioka, Hiroshi; Iguchi, Mitsutaka; Ishiguro, Nobuhisa; Nagamori, Tsunehisa; Takahashi, Satoshi; Saito, Norihiro; Tokuda, Koichi; Igari, Hidetoshi; Fujikura, Yuji; et al.
Highlilights: All carbapenemase-producing Enterobacterales (CPE) were IMP-type metallo-β-lactamase-producers. The Enterobacter cloacae complex was predominant in CPE. Klebsiella aerogenes and the Enterobacter cloacae complex were the major species in non–carbapenemase-producing (non-CP) carbapenem-resistant Enterobacterales (CRE). The 28-day mortality was comparable in both CPE and non-CP CRE groups. In CRE patients, bloodstream infections, mechanical ventilation, and cancer with metastasis were independent risk factors for 28-day mortality. ABSTRACT: Objectives: The dissemination of difficult-to-treat carbapenem-resistant Enterobacterales (CRE) is of great concern. We clarified the risk factors underlying CRE infection mortality in Japan. Methods: We conducted a retrospective, multicentre, observational cohort study of patients with CRE infections at 28 university hospitals from September 2014 to December 2016, using the Japanese National Surveillance criteria. Clinical information, including patient background, type of infection, antibiotic treatment, and treatment outcome, was collected. The carbapenemase genotype was determined using PCR sequencing. Multivariate analysis was performed to identify the risk factors for 28-day mortality. Results: Among the 179 patients enrolled, 65 patients (36.3%) had bloodstream infections, with 37 (20.7%) infections occurring due to carbapenemase-producing Enterobacterales (CPE); all carbapenemases were of IMP-type (IMP-1: 32, IMP-6: 5). Two-thirds of CPE were identified as Enterobacter cloacae complex. Combination therapy was administered only in 46 patients (25.7%), and the 28-day mortality rate was 14.3%. Univariate analysis showed that solid metastatic cancer, Charlson Comorbidity Index ≥3, bloodstream infection, pneumonia, or empyema, central venous catheters, mechanical ventilation, and prior use of quinolones were significant risk factors for mortality. Multivariate analysis revealed that mechanical ventilation (OR: 6.71 [1.42–31.6], P = 0.016), solid metastatic cancers (OR: 5.63 [1.38–23.0], P = 0.016), and bloodstream infections (OR: 3.49 [1.02–12.0], P = 0.046) were independent risk factors for 28-day mortality. Conclusion: The significant risk factors for 28-day mortality in patients with CRE infections in Japan are mechanical ventilation, solid metastatic cancers, and bloodstream infections.